Case Report: A Rare Case of Benign Recurrent Intrahepatic Cholestasis-Type 1 With a Novel Heterozygous Pathogenic Variant of ATP8B1 - Suzuki, Hiroyuki; Arinaga-Hino, Teruko; Sano, Tomoya; Mihara, Yutaro; Kusano, Hironori; Mizuochi, Tatsuki; Togawa, Takao; Ito, Shogo; Ide, Tatsuya; Kuwahara, Reiichiro; Amano, Keisuke; Kawaguchi, Toshihiro; et al. (Frontiers in Medicine, 2022)
Benign recurrent intrahepatic cholestasis type 1 (BRIC1) is a rare autosomal recessive disorder that is characterized by intermittent episodes of jaundice and intense pruritus and caused by pathogenic variants of ATP8B1. The presence of genetic heterogeneity in the variants of ATP8B1 is suggested. Herein, we describe a unique clinical course in a patient with BRIC1 and a novel heterozygous pathogenic variant of ATP8B1. A 20-year-old Japanese man experienced his first cholestasis attack secondary to elevated transaminase at 17 years of age. Laboratory examinations showed no evidence of liver injury caused by viral, autoimmune, or inborn or acquired metabolic etiologies. Since the patient also had elevated transaminase and hypoalbuminemia, he was treated with ursodeoxycholic acid and prednisolone. However, these treatments did not relieve his symptoms. Histopathological assessment revealed marked cholestasis in the hepatocytes, Kupffer cells, and bile canaliculi, as well as a well-preserved intralobular bile duct arrangement and strongly expressed bile salt export pump at the canalicular membrane. Targeted next-generation sequencing detected a novel heterozygous pathogenic variant of ATP8B1 (c.1429+2T>G). Taken together, the patient was highly suspected of having BRIC1. Ultimately, treatment with 450 mg/day of rifampicin rapidly relieved his symptoms and shortened the symptomatic period.